Paediatric Protocols For Malaysian Hospitals - Hussain Imam, Hj Muhammad Ismail; Hoong Phak, Ng; Sabeera Begum, Kader Ibrahim; Muhammad Ghazali, Ahmad Narihan; Janet Hii, Lin Yee; Yuong Chin, Tan (Malaysian Paediatric Association (MPA), 2025)
Malaysian hospitals use a set of paediatric protocols, primarily developed by the Malaysian Paediatric Association (MPA) and the Ministry of Health (MOH), to guide the care of sick children. The most recent edition is the 5th Edition, published in October 2025, which builds upon previous versions to provide evidence-based clinical guidelines for managing a wide range of conditions from general pediatrics to specific areas like neonatology and cardiology.